Don't open your eyes : a novel [large type] - Constantine, Liv (Random House Large Print, 2025)
"Annabelle Reynolds has a perfect life--loving family, fulfilling career--but is haunted by vivid dreams of a future where everything unravels. As disturbing details from her dreams begin to come true, she realizes they're not just nightmares but premonitions. When one vision shows her daughter Scarlett in imminent danger, Annabelle must race against time to uncover the truth and stop a future she's desperate to avoid. With every choice potentially fatal, she's forced to confront whether fate is fixed--or if she can change it"--